2020
DOI: 10.1002/jmv.25872
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine depletion in patients with Crimean‐Congo hemorrhagic fever

Abstract: Crimean‐Congo hemorrhagic fever (CCHF) is a viral disease. There is not enough knowledge about plasma amino acid levels in CCHF. Therefore, we investigated plasma amino acid levels in patients with CCHF and the association between the levels of these amino acids and disease severity. The plasma amino acid levels (including glutamate [Glu], aspartate [Asp], glutamine [Gln], asparagine [Asn] and gamma‐aminobutyric acid [GABA]) in CCHF patients and controls were measured by using liquid chromatography‐mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Thus, further research was conducted on whether protein catabolism increases in the muscles of COVID-19 patients. While alanine is used as a substrate for gluconeogenesis by the liver, both alanine and glutamine are converted to tricarboxylic acid intermediates by leukocytes (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, further research was conducted on whether protein catabolism increases in the muscles of COVID-19 patients. While alanine is used as a substrate for gluconeogenesis by the liver, both alanine and glutamine are converted to tricarboxylic acid intermediates by leukocytes (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the increase in serum alanine and glutamine levels in the patient group compared to the control group (p<0.0001) was significant (Table II). In studies, it is known that the immune system is activated in the acute and convalescent period in Crimean-Congo Hemorrhagic Fever patients (29). Although there is an increase in catabolic reactions in COVID-19 affected patients, the increase in serum glutamine and alanine levels suggested that there may be an increase in the use of glutamine and alanine during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma glutamine levels were highest in healthy subjects; When compared to the control group, a statistically significant decrease was observed in both the acute and covelling period patient groups (Table 2,3). Aydın et al suggested that the plasma level of glutamine decreased due to the increase in the use of glutamine in CCHF patients [8]. Increases in alanine and glutamate levels may be due to BCAA catabolism as mentioned above.…”
Section: Discussionmentioning
confidence: 97%
“…In a study conducted with CCHF patients, Aydın and colleagues. showed that plasma glutamine levels decreased in patients [8]. Due to the relationship between AA level and distribution, infectious diseases, and immune response, we investigated the levels of different AAs in the plasma of CCHF patients in the acute and convalescent period in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The body's metabolic response to COVID-19 infections has been partially demonstrated in non-targeted metabolomics studies [ 13 ]. We had been examined the metabolic responses to Crimean-Congo hemorrhagic fever virus infections and presented our findings in our previous articles [ 14 ]. Similarly, we analyzed the metabolic response to COVID-19 infections in terms of amino acid metabolism and wanted to bring it to your attention.…”
Section: Introductionmentioning
confidence: 99%